2018
DOI: 10.1364/ol.43.001059
|View full text |Cite
|
Sign up to set email alerts
|

Coherent frequency division with a degenerate synchronously pumped optical parametric oscillator

Abstract: Synchronously pumped optical parametric oscillators (OPOs) are important tools for frequency comb (FC) generation in the mid-IR spectral range, where few suitable laser gain materials exist. For degenerate OPOs, self-phase-locking to the pump FC has been demonstrated. Here, we present a phase noise study of the carrier envelope offset frequency, revealing a -6  dB reduction compared to the pump FC over a wide Fourier frequency range. These results demonstrate that a degenerate OPO can be an ideal coherent freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…7b for a singly resonant OPO. This un-equal sharing result is quite different than the degenerate case measured by Wan et al [55], where phase modulation on the pump is shown to be shared equally between the degenerate subharmonic signal and idler combs. The transfer function in Fig.…”
Section: Resultscontrasting
confidence: 92%
“…7b for a singly resonant OPO. This un-equal sharing result is quite different than the degenerate case measured by Wan et al [55], where phase modulation on the pump is shown to be shared equally between the degenerate subharmonic signal and idler combs. The transfer function in Fig.…”
Section: Resultscontrasting
confidence: 92%
“…Traditionally, OPO-based OFC is generated through synchronous pumping, in which the circulating OPO signal is periodically amplified by a MLL that is synchronized to the OPO cavity. Synchronously pumped degenerate OPOs (DOPOs) based on periodically poled Lithium niobate (PPLN) [13][14][15] and orientation-patterned gallium arsenide (OP-GaAs) [16,17] have all been successfully implemented as viable MIR OFC sources. In addition, a new operation regime of a near-synchronously pumped DOPO has been observed recently in which temporal simultons are formed through the balance between synchronization timing mismatch and nonlinear pulse acceleration [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is experimentally shown that the CEO frequency noise can be reduced by 6 dB through the half-harmonic generation. [42] In short, this work paves the way to realization of a compelling new source of ultrashort-pulse frequency combs in the midinfrared region which can benefit numerous applications, for example, spectroscopy methods that require high-power, broadband, and short-pulse MIR frequency combs. [40,41] This work sheds new lights on soliton generation based on the quadratic nonlinearity and its potential in the MIR region.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, it is experimentally shown that the CEO frequency noise can be reduced by 6 dB through the half‐harmonic generation. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%